2020
DOI: 10.1002/jso.26134
|View full text |Cite
|
Sign up to set email alerts
|

Continuing surgical care in cancer patients during the nationwide lockdown in the COVID‐19 pandemic—Perioperative outcomes from a tertiary care cancer center in India

Abstract: Background: The coronavirus disease-2019 (COVID-19) pandemic has disrupted management of non-COVID-19 illnesses, including cancer. For many solid organ cancers, surgical intervention is imperative. We present our experience with major operations during a nationwide lockdown. Method: This was an observational study of 184 patients, analyzing their perioperative outcomes and categorizing morbidity according to Clavien-Dindo Classification. Strict screening required symptomatic patients to be referred to COVID ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
(12 reference statements)
0
17
3
Order By: Relevance
“…The subgroup analysis showed that dementia was the most prevalent comorbidity followed by hypertension and Diabetes Mellitus. However, the nding of this study was contrary to other studies conducted on the prevalence of comorbidities among patients with COVID-19 where hypertension was the most prevalent comorbidity among patients with COVID-19 (21,25,45,91). This discrepancy might be explained by the inclusion of only one study in this Meta-Analysis that reported a high prevalence of dementia compared to other comorbidities.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The subgroup analysis showed that dementia was the most prevalent comorbidity followed by hypertension and Diabetes Mellitus. However, the nding of this study was contrary to other studies conducted on the prevalence of comorbidities among patients with COVID-19 where hypertension was the most prevalent comorbidity among patients with COVID-19 (21,25,45,91). This discrepancy might be explained by the inclusion of only one study in this Meta-Analysis that reported a high prevalence of dementia compared to other comorbidities.…”
Section: Discussioncontrasting
confidence: 87%
“…Body of evidence showed that patients visiting the health institution during the COVID-19 pandemic decrease signi cantly despite requiring medical care which affects signi cantly the non-COVID-19 patients' hospital admission (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body of evidence showed that patients visiting the health institution during the COVID-19 pandemic decrease signi cantly despite requiring medical care which affects signi cantly the non-COVID-19 patients' hospital admission [29][30][31][32][33].…”
mentioning
confidence: 99%
“…Some studies showed that perioperative mortality of patients with COVID-19 was very high [30,32,46,[55][56][57] while some studies failed to identify signi cant mortality among patients with COVID-19 undergoing surgical procedures [28,54,58,59].…”
mentioning
confidence: 99%